2020
DOI: 10.14744/scie.2020.87609
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiological and Laboratory Parameters on Prognosis in COVID 19 Disease

Abstract: Objective: A previously unknown contagious disease, which later turned out to be a worldwide pandemic originated from Wuhan, capital of Hubei province in China by the end of 2019. While this upheaval affected numerous countries tragically, mortality rate and necessity for ICU were relatively low in Turkey. Methods: A total of 166 patients (65 at ICU, 101 at pandemic service) were analyzed to uncover effect of radiological and laboratory parameters on prognosis in COVID-19. One hundred and one patients (60.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
2
0
0
1
Order By: Relevance
“…In a study by Ozer et al with 166 patients, lung computed tomography involvement was found in 60.8% of COVID-19 patients hospitalized in the pandemic ward [25]. In this study, lung computed tomography involvement was detected in 59.4% of the patients followed up with the diagnosis of COVID-19 in the pandemic service, supporting the literature.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Ozer et al with 166 patients, lung computed tomography involvement was found in 60.8% of COVID-19 patients hospitalized in the pandemic ward [25]. In this study, lung computed tomography involvement was detected in 59.4% of the patients followed up with the diagnosis of COVID-19 in the pandemic service, supporting the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Thorax CT is frequently used in the diagnosis of COVID-19 pneumonia, in the course of the disease, in demonstrating progression and residual disease. The stages of radiological recovery in patients with COVID-19 pneumonia were reported by Akçay, et al [9]. In the initial phase (0-4 days), the main CT finding is ground glass density in the bilateral or In conclusion, we found that a high level of D-dimer in patients with COVID-19 was associated with thorax CT severity score.…”
Section: Discussionsupporting
confidence: 80%
“…Hastalığın tespitinde ters transkripsiyon polimeraz zincir reaksiyonu (rt-PCR) testi, hastalığın erken evrelerinde veya düşük yüklü örneklerde yeterli duyarlılığa (% 60 -70) sahip olmasa da Covid-19'un tanısında kabul edilen standart referanstır (Fang et al, 2020). Öte yandan, yüksek duyarlılığı (% 98) nedeniyle bilgisayarlı tomografi (BT) görüntüleme ile de Covid-19'un akciğerdeki şiddeti ve seyri takip edilebilmektedir (Ai et al, 2020, Akbaş 2021, Ozer 2020, Cömert 2020. Bu nedenle Covid-19 hastalığının hızlı ve yüksek hassasiyette tespitinde, pulmoner evresinin radyologlar tarafından değerlendirilmesinde ve hastaların uygun triyajında BT görüntüleme çok önemli bir rol oynamaktadır.…”
Section: Introductionunclassified